Cadangan Kerugian Penurunan Nilai, Risiko Kredit, dan Kinerja Keuangan Perbankan Setelah Implementasi PSAK 71 - Rima Fadila (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
The impairment of financial assets, credit risk, and banking performance are important topics in the banking industry that have undergone significant changes following the implementation of the Financial Accounting Standards Statement (PSAK) 71. PSAK 71, adopted to replace PSAK 55, requires banks to account for the allowance for im-pairment losses (CKPN) based on the more proactive expected credit loss (ECL) model, which takes into account potential future losses. This study aims to provide a literature review on the impact of PSAK 71 implementation on the allowance for impairment losses, credit risk, and banking financial performance. Based on the existing literature, it was found that the application of PSAK 71 can enhance transparency in managing credit risk, although it may put pressure on the bank's financial performance in the short term due to the higher allowance for impairment. Furthermore, more measurable credit risk and better risk management are expected to positively impact the stability and resilience of the banking sector in the long term.